2015
DOI: 10.15376/biores.10.2.3277-3292
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carbonation Conditions on the Properties of Carbohydrate-Calcium Carbonate Hybrid Pigments

Abstract: The influence of two polysaccharides, native corn starch and carboxymethyl cellulose (CMC), on the precipitation of calcium carbonate was examined by utilizing two different carbonation processes. In a batch process, carbon dioxide gas was fed through calcium hydroxide slurry at pH 11.5 to 12.0. The reaction was complete when the pH had been decreased to 7. In a fed-batch reaction, the carbon dioxide was dissolved in water while calcium hydroxide was pumped into the water, maintaining a constant pH of 6.0±0.5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Many efforts to improve reproducibility and control the calcium carbonate properties included the addition of various excipients to the precipitation reaction. When used as a pigment material, the addition of CMC was shown to affect calcium carbonate particle morphology, improve optical performance, and reduce particle mechanical strength, which can be further improved by supplementation with corn starch [18]. In another study, CMC was shown to induce spherical particle formation [14] and contribute negative charges, thus making the particles suitable as templates for LbL deposition [12].…”
Section: Discussionmentioning
confidence: 99%
“…Many efforts to improve reproducibility and control the calcium carbonate properties included the addition of various excipients to the precipitation reaction. When used as a pigment material, the addition of CMC was shown to affect calcium carbonate particle morphology, improve optical performance, and reduce particle mechanical strength, which can be further improved by supplementation with corn starch [18]. In another study, CMC was shown to induce spherical particle formation [14] and contribute negative charges, thus making the particles suitable as templates for LbL deposition [12].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, handsheets fabricated with chitosan-induced aggregated fillers are seen to improve tensile strength by 8.2% compared to native ones. Enhancement or negative impact of paper strength with different pre-flocs or bio-based composite mineral fillers is well verified by many authors [4,8,60].…”
Section: Handsheet Preparation and Characterizationmentioning
confidence: 72%
“…Industrial low-cost native starch or cationic starch is a widely accepted biopolymer in filler modification among various researchers as this hydrogen bonding polymer can develop strong bonds with pulp fibers when dried after starch/mineral composite fillers are added to the furnish. Another approach to fabricate these bio-based composite fillers with paper sheet is in situ crystallization of calcium carbonate in the presence of biopolymers [8]. But there are certain limitations associated with starch such as consumption of extra chemicals during the coating process, loss of cationicity at alkaline pH, sensitivity to water and its prone to microbial attack [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation